Cloning of cDNA encoding Drosophila poly(ADP-ribose) polymerase: leucine zipper in the auto-modification domain. - Uchida, K (1993)
We have isolated cDNA clones for a Drosophila poly(ADP-ribose) polymerase (PARP; EC 2.4.2.30) by screening a lambda gt11 cDNA library with a Drosophila partial cDNA fragment. The Drosophila PARP probe was obtained by the polymerase chain reaction with heterologous primers deduced from conserved amino acids in the mammalian, chicken, amphibian, and fish sequences. The Drosophila PARP mRNA is 3.2 kb in length and is expressed in the early stages of development. The PARP protein of 994 amino acids contains two zinc-finger motifs and an NAD-binding motif, which are conserved among different species. Interestingly, the heptad leucine repeat in an alpha-helix was found in Drosophila PARP. Alignments of the auto-modification domains of various species showed the repeated hydrophobic amino acids on the same face of the helix that make the coiled-coil configuration in the mammalian and chicken sequences. The presence of a leucine-zipper motif in the auto-modification domain suggests that this motif might be responsible for protein-protein interaction between PARP and physiological acceptors. PARP may have novel functions, possibly involving its homo- and/or heterodimerization with other nuclear leucine-zipper proteins and its regulation by ADP-ribosylation.